PENGARUH PEMBAYARAN ZAKAT PERTANIAN TERHADAP KESEJAHTERAAN MASYARAKAT DESA SUMBERJO KIDUL-BOJONEGORO (Kajian Sosial Hukum Islam) - Budi al-Ashad (LPPM UNHASY, 2016)
Since the early Islam, zakat be on improving the welfare of Muslims. With charity funds, an economic needs of the Muslim community can be met. Zakat rules in the era of Prophet Muhammad life are not entirely cover and insufficient development of the Muslim community spread across the world with different geographical conditions. In the village Sumberjokidul Sukosewu Bojonegoro with a majority population of rice farming, zakat issued by muzakki does not seem helpful to the welfare of the community. In addition there are other factors that do not encourage the public welfare, understanding different religions to be a factor of how muzakki pay zakat from the his mal zakawi.Keyword: zakat, welfare, understanding to religion rule of zakat.